2022
DOI: 10.1161/circheartfailure.121.009085
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pulmonary Artery Pulsatility Index With Adverse Cardiovascular Events Across a Hospital-Based Sample

Abstract: Background: The pulmonary artery pulsatility index (PAPi), calculated from the ratio of the pulmonary artery pulse pressure to right atrial pressure, is a predictor of right ventricular failure after inferior myocardial infarction and left ventricular assist device implantation. Whether PAPi is associated with adverse outcomes across a heterogeneous population is unknown. Methods: We examined consecutive patients undergoing right heart catheterization b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Low PAPi has previously been shown to be associated with higher mortality in select samples including post-myocardial infarction, pulmonary arterial hypertension, and advanced heart failure populations [12-17]. We recently demonstrated that lower PAPi was associated with increased risk of adverse events including all-cause mortality, MACE, and HF hospitalizations across a much wider spectrum of cardiopulmonary disease [18]. Similarly, RA:PCWP ratio as an index for RV function has also been demonstrated as a marker for in-hospital mortality [19].…”
Section: Discussionmentioning
confidence: 99%
“…Low PAPi has previously been shown to be associated with higher mortality in select samples including post-myocardial infarction, pulmonary arterial hypertension, and advanced heart failure populations [12-17]. We recently demonstrated that lower PAPi was associated with increased risk of adverse events including all-cause mortality, MACE, and HF hospitalizations across a much wider spectrum of cardiopulmonary disease [18]. Similarly, RA:PCWP ratio as an index for RV function has also been demonstrated as a marker for in-hospital mortality [19].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of RVF is based on the extent of ventricular impairment, using the central venous pressures (CVP), pulmonary capillary wedge pressure (PCWP) [ 13 ], pulmonary-artery-pulse-pressure-to-right-atrial-pressure ratios (PAPi) ( ) [ 14 ] and right ventricular stroke work index (RVSWI) ( ) [ 15 ] as indicators [ 16 ] ( Figure 1 ).…”
Section: Definition and Classification Of Cardiogenic Shockmentioning
confidence: 99%
“…PAPi < 0.9 is a predictor of RV failure after LV assist device implantation. Although primarily validated in patients with CS following inferior AMI, it may aid in escalating and weaning therapies in HR‐PCI patients 22 …”
Section: Roadmap Towards a High‐risk Percutaneous Coronary Interventi...mentioning
confidence: 99%
“…Generally, SBP > 90 mmHg, MAP > 60 mmHg, CI > 2.2 L/min/m 2 , CPO > 0.6 W, and LVEDP < 15 mmHg are indicators of haemodynamic recovery, facilitating careful weaning from MCS. In patients with Swan–Ganz catheter, PAPi > 0.9 is a predictor of appropriate RV function 22 . A step‐by‐step algorithm for weaning from Impella is shown in Figure and has been described in the Step 3: Percutaneous Coronary Intervention with Impella section.…”
Section: Roadmap Towards a High‐risk Percutaneous Coronary Interventi...mentioning
confidence: 99%